Seiland - Bjorvand, Harald; Theil, Rolf (NAMN OG NEMNE, 2020)
The large island which bears the name Seiland is situated in the western part of Finnmark in the municipalities Alta, Hammerfest and Kvalsund. The corresponding North Saami name is Sievju, which reflects Proto-Saami *sievjÅ or *siepjÅ. If these forms were to be regarded as borrowed from Proto-Scandinavian like so many other words in North Saami, then *sievjÅ would reflect e.g. PrScand. nom. *seuju or nom. *segju, and *siepjÅ would be a reflex of e.g. PrScand. nom. *sebju. These forms are however unacceptable. Because of the so-called older i/j-umlaut of Gmc. *e > *i we expect Proto-Scandinavian forms like *siuju, *sigju and *sibju. These hypothetical forms cannot have given the first part Sei- of Seiland (-land is a later addition). It also proved impossible to reconstruct an acceptable Old Norse (or Proto-Scandinavian) proto-form of Sei-, which should consequently best be regarded as an early adoption (in the sixth century?) of North Saami Sievju. On the other hand the assumed Proto-Saami forms *sievjÅ and *siepjÅ do not seem to have any cognates in North Saami. In addition, these Proto-Saami forms cannot be reflexes of any Pre-Saami forms. Proto-Saami *sievjÅ and *siepjÅ had to be reflexes of Pre-Saami *sevjÉ” or *sepjÉ”, which, however, are phonotactically unacceptable. Because of the so-called a/É”-umlaut, Proto-Saami-Finnic first syllable *e changed into Pre-Saami *É› when the second syllable had *a or *É”. *É› became ea in modern North Saami. Like so many names and words in this language they are therefore in all probability borrowed from the unknown Palaeo-Laplandic languages (Aikio) which were spoken in these parts before the westward spread of the Saami languages.